Proceedings of the 29th ACM International Conference on Multimedia 2021
DOI: 10.1145/3474085.3475374
|View full text |Cite
|
Sign up to set email alerts
|

LSTC: Boosting Atomic Action Detection with Long-Short-Term Context

Abstract: In this paper, we place the atomic action detection problem into a Long-Short Term Context (LSTC) to analyze how the temporal reliance among video signals affect the action detection results. To do this, we decompose the action recognition pipeline into shortterm and long-term reliance, in terms of the hypothesis that the two kinds of context are conditionally independent given the objective action instance. Within our design, a local aggregation branch is utilized to gather dense and informative short-term cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In place of the double-branch approach, Christoph [19] presented an extended 3D convolutional network (X3D), which gradually modifies the model's width parameter to require less computational work while producing superior results. Li et al [20] analyzed the effect of time dependence on behavior detection by placing the behavior detection in a Long-Short Term Context (LSTC).…”
Section: Video Behavior Detectionmentioning
confidence: 99%
“…In place of the double-branch approach, Christoph [19] presented an extended 3D convolutional network (X3D), which gradually modifies the model's width parameter to require less computational work while producing superior results. Li et al [20] analyzed the effect of time dependence on behavior detection by placing the behavior detection in a Long-Short Term Context (LSTC).…”
Section: Video Behavior Detectionmentioning
confidence: 99%
“…Table 1 shows the comparison results between the proposed methods and the SOTA methods SlowFast R‐50 and SlowFast R‐101‐NL, 41 MviT‐B‐24, 46 AVSF, 44 LSTC, 47 X3D‐XL 45 on AVA2.2 data set. It is observed that the proposed method outperforms other methods, with the original ACAR algorithm being 30.5% and the mAP of the proposed network being increased to 30.7%.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Comparison Results of the overall performance of SlowFast, R‐50, 41 SlowFast, R‐101‐NL, 41 M‐viT‐B‐24, 46 AVSF, 44 LSTC, 47 X3D‐XL 45 on the AVA2.2 data set. [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation